NEUT-SFL in Patients with COVID-ARDS: A Novel Biomarker for Thrombotic Events? - Laure Stiel (Hindawi Limited, 2021)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an enveloped RNA virus first identified in December 2019 in Wuhan, China, and responsible for coronavirus disease 2019 (COVID-19). The ongoing COVID-19 pandemic is impacting healthcare worldwide. Patients who develop coagulopathy have worse outcomes. The pathophysiology of COVID-19 suggests a strong interplay between hemostasis and immune cells, especially neutrophils. Our purpose was to assess neutrophil fluorescence as a potential biomarker of deep vein thrombosis (DVT) in patients with COVID-acute respiratory distress syndrome (COVID-ARDS). Sixty-one patients with COVID-ARDS admitted to the four intensive care units (ICUs) of a French general hospital were included in this prospective study. Neutrophil activation was assessed by measuring neutrophil fluorescence (NEUT-Side Fluorescence Light, NEUT-SFL) with a specific fluorescent dye staining analyzed by a routine automated flow cytometer Sysmex XN-3000™ (Sysmex, Kobe, Japan). DVT was diagnosed by complete duplex ultrasound (CDU). We found that NEUT-SFL was elevated on admission in patients with COVID-ARDS (49.76 AU, reference value 46.40 AU, p<0.001), but did not differ between patients with DVT (49.99 AU) and those without (49.52 AU, p=0.555). NEUT-SFL is elevated in patients with COVID-ARDS, reflecting neutrophil activation, but cannot be used as a marker of thrombosis. Because neutrophils are at interface between immune response and hemostasis through release of neutrophil extracellular traps, monitoring their activation could be an interesting approach to improve our management of coagulopathy during COVID-ARDS. Further research is needed to better understand the pathophysiology of COVID-19 and identify high-performance biomarkers.